Justiça do capital: violência estrutural nas relações de trabalho dos eletricitários em Minas Gerais - Tardeli, Everson de Alcântara [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This work aims to analyze how structural violence of capital manifests itself through the companies and the Labor Court. Therefore, it consists in analyzing the performance of a particular Regional Labor Court in some specific cases of strikes and collective bargaining, allowing understand its bias in the reconciliation and judgment in favor of the employer class. So, it looks specifically at the role of Regional Labor Court of 3rd Region (TRT/MG) in cases of collective bargaining and electricity segment strikes in Minas Gerais ( Cemig) and the main trade union representatives of the employees of this company, i.e. Electricity Workers „Union of South Minas Gerais (SINDSUL/MG) and Electricity Workers‟ Union of Minas Gerais (SINDIELETRO/MG), also including some other companies, unions and courts, that contributes to a necessary contextualization. It empirically identifies major points of conflict, negotiation strategies and correlation of forces between these social actors. It displays the concreteness of the three social actors objects of research, making a historical approach about the rule of capital and labor relations, allowing that, at least, we understand the materiality of its existence by the development of societies, culminating on the birth of the bourgeois Brazilian state and its Labor Court (especially the TRT/MG), CEMIG and the SINDSUL/MG. As element of reflection, it presents a historical discussion about the development of capitalism in the post war, from Keynesianism to Neoliberalism, and their reflections in Brazil. It also summarizes the position of Brazilian labor movement in this context. It shows the performance of each actor of the plot proposed here, as well as the centrality of some aspects present in the collective negotiations of neoliberal period, discussing the situation lived by electricity workers as result of these actions. Then, it‟s noted the increase of adding value rates, the number of occupational...

Este trabalho tem por objetivo analisar como se manifesta a violência estrutural do capital por meio das empresas e da Justiça do Trabalho. Consiste, portanto, na análise de atuação de um determinado Tribunal Regional do Trabalho em alguns casos específicos de greves e dissídios coletivos possibilitando compreender sua parcialidade nas conciliações e julgamentos em favor da classe patronal. Por isso, analisa especificamente a atuação do Tribunal Regional do Trabalho da 3ª Região (TRT/MG) nos casos de dissídios coletivos e greves dos eletricitários de Minas Gerais, envolvendo os conflitos entre a Companhia Energética de Minas Gerais (CEMIG) e os principais sindicatos representantes dos trabalhadores desta empresa, ou seja, Sindicato dos Eletricitários do Sul de Minas Gerais (SINDSUL/MG) e Sindicato dos Eletricitários de Minas Gerais (SINDIELETRO/MG), incluindo, ainda, algumas outras empresas, sindicatos e tribunais na medida em que contribui para uma contextualização necessária. Identifica empiricamente os pontos de maior conflito, as estratégias de negociação e as correlações de forças entre estes atores sociais. Apresenta a concretude dos três atores sociais objetos da pesquisa, fazendo uma abordagem histórica sobre A ordem do capital e as relações de trabalho, o que permite compreendermos minimamente a materialidade de sua existência a partir do desenvolvimento das sociedades, culminando no nascimento do Estado burguês brasileiro e de sua Justiça do Trabalho (especialmente o TRT/MG), da CEMIG e do SINDSUL/MG. Apresenta uma discussão histórica como elemento de reflexão sobre o desenvolvimento do capitalismo do pós guerras, do keynesianismo ao neoliberalismo, e seus reflexos no Brasil. Sintetiza, também, o posicionamento do sindicalismo brasileiro neste contexto. Demonstra a atuação de cada um dos atores da trama aqui proposta, bem como a centralidade de alguns...
Keywords: Companhia Energética de Minas Gerais; Serviço social; Responsabilidade social da empresa - Brasil; Justiça do trabalho; Sindicalismo; Sindicatos - Dirigentes e empregados; Trabalho - Aspectos sociais; Trabalhadores - Aspectos jurídicos; Relações trabalhistas - Minas Gerais (Estado); Social service